2015
DOI: 10.1177/0040517515578329
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between particulate soil removal and surface properties of laundry detergent solutions

Abstract: The purpose of this study is to correlate surface properties of laundry detergents and model surfactant solutions with their washing abilities. For the study, laundry detergents available on the Polish market were selected and categorized according to their retail price: the cheapest (P1, P2, P3), average priced (P4, P5, P6, P7, P8) and the most expensive (P9, P10). Anionic sodium dodecylbenzenesulfonate and nonionic nonaethylene glycol monodecyl ether were used for the preparation of the model solutions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…It was also observed that the addition of 2-butanol or 1-decanol demonstrated higher contact angle values corresponding to poorer cold water detergency. This is consistent with Kalak and Cierpiszewski (2015) who found that the good detergency of activated carbon (a particulate soil) in various surfactant systems was highly related to a low contact angle. Contact angle is thus identified as an important parameter for design of optimized detergency formulations in cold water detergency of semisolid soils.…”
Section: The Effect Of Surfactant Systems On Alcohol Selectionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was also observed that the addition of 2-butanol or 1-decanol demonstrated higher contact angle values corresponding to poorer cold water detergency. This is consistent with Kalak and Cierpiszewski (2015) who found that the good detergency of activated carbon (a particulate soil) in various surfactant systems was highly related to a low contact angle. Contact angle is thus identified as an important parameter for design of optimized detergency formulations in cold water detergency of semisolid soils.…”
Section: The Effect Of Surfactant Systems On Alcohol Selectionsupporting
confidence: 91%
“…However, contact angle values in this current study were slightly different. This variation somewhat depends on the properties of surfactants, fabric, and soil studied (Kalak and Cierpiszewski, ). It was also observed that the addition of 2‐butanol or 1‐decanol demonstrated higher contact angle values corresponding to poorer cold water detergency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfactants have been used as one of the active components in laundry detergents because they can reduce surface tension, interfacial tension (IFT), and also increase the wettability of the substrate surface, thereby enhancing the cleaning process (Charoensaeng et al, 2008;Kalak and Cierpiszewski, 2015;Rosen and Kunjappu, 2004;Witthayapanyanon et al, 2010). Anionic surfactants have been widely used in cleaning applications due to temperature insensitivity (Velásquez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Finland only a few surveys exist, and the most recent was published in 2002 (Aalto, ). In many studies, the focus has been on environmentally friendly washing and laundry procedures as well as washing technology and agents in processes, such as decreasing the use of energy, water, and amounts of chemicals ( Honisch, Stamminger, & Bockmühl, ; Abeliotis et al, ; Cameron, ; Gooijer & Stamminger, ; Hellmut & Dreja, ; Kalak & Cierpiszewski, ; Kruschwitz, Ausburg, & Stamminger, ; Laitala & Kjeldsberg, ; Laitala et al, ; Lambert et al, ; Scheid et al, ; Schmitz & Stamminger, ).…”
Section: Introductionmentioning
confidence: 99%